Revisiting the Accelerated Internationalization of Emerging Market SMEs : The Roles of Firms’ Collaborations and Environmental Management Practices - Zahoor, Nadia; Donbesuur, Francis; Khan, Zaheer; Tarba, Shlomo Y.; Cooper, Cary L. (MDPI, 2023)
Although the performance implications of inter- and intra-firm collaborations have been discussed by prior studies, how such collaborations can drive the accelerated internationalization of small and medium-sized enterprises (SMEs) originating from emerging markets remains unclear. This study was, thus, aimed at shedding light on this relationship by drawing insights from the resource-based view (RBV). We argued that the interaction between inter- and intra-firm collaborations can drive accelerated internationalization through environmental management practices. We, thus, developed and tested a conceptual framework by performing structural equation modeling on a sample of 208 SMEs based in the United Arab Emirates (UAE). Our findings reveal that the interaction between inter- and intra-firm collaborations is indeed conducive to accelerated internationalization. More importantly, we found that environmental management practices mediate the relationship between such interaction and accelerated internationalization. Our findings have important implications for international entrepreneurship research and practice in relation to how environmental management practices can enhance such a relationship.
Keywords: intra-firm collaboration; inter-firm collaboration; environmental management practices; accelerated internationalization; SMEs; emerging markets